Overview of the international research on sports for people with disabilities - Pan, H. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction Understanding the current status of international sports research for people with disabilities assists in the expansion of knowledge in the field. This information will permit the identification of research questions with the aim to reach new conclusions and update current theoretical models. In the era of economic globalization, political multi-polarization and multi culturalism, disability in sports presents new characteristics which should be studied. The present findings will provide important information to exercise professionals and human rights researchers. The The present study will also advance knowledge of international sports research for people with disabilities. Methods Methods used included a review of the literature and comparative analysis. Results International sports for people with disabilities have developed rapidly in recent times. There are increasing numbers of disabled individuals participating in the sports and competition levels have improved continuously. Similarly, the organization and regulations of special sports games have improved considerably. The Paralympic Games is now one of top international sport events for people with disabilities. Many countries have recognized the important role of disabled sports in the development of civilization and for the security of human rights. In addition, there is now a trend to merge disabled sport with sports for able-bodied persons. This includes the sharing of sports resources, and even being trained together with able-bodied professional athletes. Moreover, the materials of making artificial prosthesis are now more portable and firmer. Advancements are continuing in science and technology which will be applied to disabled sports. Conclusions Although the social systems and the development of the economy vary across countries, there are many common elements regarding disability in sport. The goals of disabled sports are to further develop the sports and emphasize involvement instead of competition. The majority of countries have made legislation to guarantee employment and rehabilitation opportunities for people with a disability, including some regulations which relate to sports.. Progress for disabled sports has been made with the U.N and other international disability organizations working together to increase communication and collaboration at the organizational, national and global levels.